Involvement of Netrins and Their Receptors in Neuronal Migration in the Cerebral Cortex - Yamagishi, Satoru; Bando, Yuki; Sato, Kohji (Frontiers in Cell and Developmental Biology, 2021)
Excitatory cortical neurons develop from proliferative epithelium in the ventricular zone and migrate radially to the cortical plate, whereas inhibitory GABAergic interneurons are born in the ganglionic eminence and migrate tangentially. The migration of newly born cortical neurons is tightly regulated by both extracellular and intracellular signaling to ensure proper positioning and projections. In this article, we review the axon guidance molecules that regulate neuronal migration, focusing on netrin family proteins, their receptors, and related molecules, including neogenin, repulsive guidance molecules (RGMs), down syndrome cell adhesion molecule (DSCAM), fibronectin leucine-rich repeat transmembrane proteins (FLRTs), and draxin. Netrin proteins induce attractive and repulsive signals depending on their receptors. For example, binding of netrin-1 to deleted in colorectal cancer (DCC), possibly together with Unc5, repels migrating GABAergic neurons from the ventricular zone of the ganglionic eminence, whereas binding to 31 integrin promotes cortical interneuron migration. Human genetic disorders associated with these and related guidance molecules, such as congenital mirror movements, schizophrenia, and bipolar disorder, are also discussed.